2018
DOI: 10.1111/1744-7941.12205
|View full text |Cite
|
Sign up to set email alerts
|

Towards better work in China: mapping the relationships between high‐performance work systems, trade unions, and employee well‐being

Abstract: Human resource management (HRM) is a major mechanism to realise decent work and achieve employee well‐being in China. Key questions concern how and when HRM is mutually beneficial for employers and employees, particularly how well HRM works with trade unions in achieving decent work. This study examines the effect of high‐performance work systems and trade unions on employee engagement, paying particular attention to the role of industrial relations (IR) climate in facilitating this relationship. Hypotheses we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 76 publications
2
21
0
2
Order By: Relevance
“…The second hypothesis that postulated the positive indirect influence of OBSE between the relationship of HPWPs and outcomes of employees was also supported. The findings of this hypothesis were in line with the findings of Yang et al (2019). Furthermore, COR theory also supported that vital resources produce a positive impact on the work outcomes of employees.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…The second hypothesis that postulated the positive indirect influence of OBSE between the relationship of HPWPs and outcomes of employees was also supported. The findings of this hypothesis were in line with the findings of Yang et al (2019). Furthermore, COR theory also supported that vital resources produce a positive impact on the work outcomes of employees.…”
Section: Discussionsupporting
confidence: 83%
“…Recent studies revealed the influential role of HPWPs in human resource management strategies in Western culture; however, limited studies have explored its impact on developing economies (Cooke, 2018;Cooke et al, 2019). Past literature emphasized the potential effect of HPWPs on task performance (Topcic et al, 2016;Cooper et al, 2019;Jeong and Shin, 2019;Yang et al, 2019). Furthermore, researchers conceded a need to explore how HPWPs facilitate extra roles and performances of employees (Karadas and Karatepe, 2019).…”
Section: High-performance Work Practices Eirp and Etpmentioning
confidence: 99%
See 1 more Smart Citation
“…For the quantitative studies, only a small proportion are contextualized in the institutional setting (Ngo, Lau, & Foley, 2008; Wei & Lau, 2011), or include institutional actors and industrial/employment relations as an element of the research, even though employment/labor market conditions in China vary significantly across industrial sectors and differ between China and other economies, which may influence the effect of SHRM practices (Lepak et al, 2007). Yang et al's (2019) study that explores the relationships between HPWS, trade unions and employee well‐being is one of the few exceptions. Similarly, Zhou, Fan and Son's (2019, p. 253) study of 108 firms and 1,250 employees offers another good example that bridges the HRM and employment relations literature by “investigating how human capital and employee participation, direct voice mechanism, and corporate governance participation jointly moderate the relationship between HPWS and organizational innovation.” By contrast, qualitative SHRM studies are generally better contextualized (Zhang & Albrecht, 2010).…”
Section: Studies Of Shrm In the Chinese Contextmentioning
confidence: 99%
“…HPWS plays a role in fostering decent work and working conditions for employees. (Yang et al, 2019). HPWS utilities may vary in dynamic environments.…”
Section: Introductionmentioning
confidence: 99%